A Detailed Clinicopathologic Study of ALK-translocated Papillary Thyroid Carcinoma. (May 2015) - Chou, Angela; Fraser, Sheila; Toon, Christopher W.; Clarkson, Adele; Sioson, Loretta; Farzin, Mahtab; Cussigh, Carmen; Aniss, Ahmad; O'Neill, Christine; Watson, Nicole; Clifton-Bligh, Roderick J.; Learoyd, Diana L.; et al.
<x xml:space="preserve">Abstract</x> Pathogenic ALK translocations have been reported in papillary thyroid carcinoma (PTC). We developed and validated a screening algorithm based on immunohistochemistry (IHC), followed by fluorescence in situ hybridization (FISH) in IHC-positive cases to identify ALK-rearranged PTC. IHC and FISH were performed in a cohort of 259 thyroid carcinomas enriched for aggressive variants. IHC was positive in 8 cases, 6 confirmed translocated by FISH (specificity 75%). All 251 IHC-negative cases were FISH negative (sensitivity 100%). Having validated this approach, we performed screening IHC, followed by FISH in IHC-positive cases in an expanded cohort. ALK translocations were identified in 11 of 498 (2.2%) of all consecutive unselected PTCs and 3 of 23 (13%) patients with diffuse sclerosing variant PTCs. No ALK translocations were identified in 36 PTCs with distant metastases, 28 poorly differentiated (insular) carcinomas, and 20 anaplastic carcinomas. All 14 patients with ALK translocations were female (P=0.0425), and translocations occurred at a younger age (mean 38 vs. 48 y, P=0.0289 in unselected patients). ALK translocation was an early clonal event present in all neoplastic cells and mutually exclusive with BRAFV600E mutation. ALK translocation was not associated with aggressive clinicopathologic features (size, stage, metastasis, vascular invasion, extrathyroidal extension, multifocality, risk for recurrence, radioiodine resistance). We conclude that 2.2% of PTCs are ALK-translocated and can be identified by screening IHC followed by FISH. ALK translocations may be more common in young females and diffuse sclerosing variant PTC but do not connote more aggressive disease.